2010
DOI: 10.1186/1297-9686-42-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of resistance to salmonellosis and to Salmonella carrier-state in fowl: a review

Abstract: Salmonellosis is a frequent disease in poultry stocks, caused by several serotypes of the bacterial species Salmonella enterica and sometimes transmitted to humans through the consumption of contaminated meat or eggs. Symptom-free carriers of the bacteria contribute greatly to the propagation of the disease in poultry stocks. So far, several candidate genes and quantitative trait loci (QTL) for resistance to carrier state or to acute disease have been identified using artificial infection of S. enterica serova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 74 publications
1
79
0
2
Order By: Relevance
“…Indeed, differences in expression of gallinacins observed by Sadeyen et al, (2004) and Sadeyen et al (2006) were found to be associated, in young chicken, with increased susceptibility but, in adults, with resistance. Similar variations with age should also be the case of a large proportion of genes or genome regions found to be involved in resistance (for a review, see Calenge et al, 2010). This result also implies that increasing genetic resistance of hens should reduce resistance in chicks.…”
Section: Response To Selectionmentioning
confidence: 87%
See 2 more Smart Citations
“…Indeed, differences in expression of gallinacins observed by Sadeyen et al, (2004) and Sadeyen et al (2006) were found to be associated, in young chicken, with increased susceptibility but, in adults, with resistance. Similar variations with age should also be the case of a large proportion of genes or genome regions found to be involved in resistance (for a review, see Calenge et al, 2010). This result also implies that increasing genetic resistance of hens should reduce resistance in chicks.…”
Section: Response To Selectionmentioning
confidence: 87%
“…One main feature of studies of genetic resistance to Salmonella is the very large number of resistance-related traits that were considered (see Calenge et al, (2010) for a review). They differ in many factors.…”
Section: Development Of Protocols Of Measures and Identification Of Gmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 2,500 serotypes have been described mostly under the species (3,4). Salmonellosis, especially the one that manifests as Pullorum disease, is one of the commonest diseases of local poultry, which causes severe economic loss to the industry.…”
Section: Introductionmentioning
confidence: 99%
“…More than 2.550 Salmonella serotypes have been reported, mostly belonging to S. enterica [2] . Pullorum disease caused by S. enterica serovar.…”
Section: Introductionmentioning
confidence: 99%